х=37\51
Пошаговое объяснение:
(X-12/17)*9=3/17
х-12\17= 3\17 : 9 3\17 : 9= 3\17* 1\9= 1\51
х- 12\17= 1\51
х= 1\51 +12\17 1\51 +12\17 =1\51 +(12*3)\(17*3)=1\51+36\51=37\51
(37\51 -12\17)*9=3\17
(37\51- 36\51)*9=3\17
1\51*9=3\17
3\17=3\17
Решение и ответ:
х=37\51
Пошаговое объяснение:
(X-12/17)*9=3/17
х-12\17= 3\17 : 9 3\17 : 9= 3\17* 1\9= 1\51
х- 12\17= 1\51
х= 1\51 +12\17 1\51 +12\17 =1\51 +(12*3)\(17*3)=1\51+36\51=37\51
х=37\51
(37\51 -12\17)*9=3\17
(37\51- 36\51)*9=3\17
1\51*9=3\17
3\17=3\17
Решение и ответ: